Narrativas de la experiencia de ser víctimas de violencia por parte de su pareja en un grupo de mujeres del municipio de Zarzal Valle: Una posibilidad de mediación - Ossa Trejos, Natalia (Universidad Antonio Nariño, 2023)
In the present investigation, a study focused on the narratives of the experience of being victims of violence by their partner in a group of women from the municipality of Zarzal Valle was carried out: A possibility of mediation. For this, a qualitative methodology was used that allowed the execution of a phenomenological design evidencing the stories of the victims through their experiences on this family problem and therefore social; The technique used for data collection was the semi-structured (individual) interview. T